TREND AND SPATIAL ANALYSIS OF DIABETES MELLITUS DISEASE 2019-2023 IN YOGYAKARTA CITY - Setiyaningrum, Annisa; Solikhah, Solikhah; Sulistyawati, Sulistyawati (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Diabetes is a non-communicable disease that can cause complications. It is characterized by elevated blood sugar levels. This study aimed to map out the trends and characteristics of diabetes mellitus (DM), especially type 2 DM, in Yogyakarta City in 2019-2023. This study employed a quantitative descriptive methodology, utilizing a cross-sectional approach. Data on patients with diabetes mellitus were obtained from the Yogyakarta City Health Office. The population of this study was all data of patients with type 2 DM who visited the health center in Yogyakarta City. Total sampling was used to select research participants. The study was conducted in May-June 2024. Descriptive analysis was processed using SPSS 26, while area mapping used the QGIS application version 3.36.1. According to the study's findings, the majority of Yogyakarta City area's type 2 diabetes patients between 2019 and 2023 were female. Type 2 diabetes happens in people over 45 years of age. Between 2019 and 2023, there was a rise in type 2 diabetes cases. Between 2019 and 2023, there was a rise in type 2 diabetes cases. Geographically, Danurejan District had the highest prevalence of type 2 diabetes in 2019 and 2023, whereas Gedong Tengen District had the highest prevalence in 2020–2022. Promotion of a healthy diet, regular exercise, early screening, and diabetes education in Indonesia is necessary.